2017
DOI: 10.3390/ijms18051014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin and Its Analogues on Pancreatic Inflammation, Enzyme Secretion, and Tumorigenesis

Abstract: Melatonin is an indoleamine produced from the amino acid l-tryptophan, whereas metabolites of melatonin are known as kynuramines. One of the best-known kynuramines is N1-acetyl-N1-formyl-5-methoxykynuramine (AFMK). Melatonin has attracted scientific attention as a potent antioxidant and protector of tissue against oxidative stress. l-Tryptophan and kynuramines share common beneficial features with melatonin. Melatonin was originally discovered as a pineal product, has been detected in the gastrointestinal trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 90 publications
(150 reference statements)
1
32
0
2
Order By: Relevance
“…11 Reportedly, the main source of melatonin is the gastrointestinal tract, with estimated production over 400 times higher than that in the pineal gland. 12 The indoleamine has great pharmacological promise as an antioxidant enzyme that can scavenge free radicals, and protect from oxidative damage. 13,14 Previous studies has shown that melatonin can inhibit the proliferation of various human cancers, including leukemia, 15,16 hepatocarcinoma, 17 breast cancer, 18 colorectal cancer, 19,20 lung cancer, 21,22 and gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…11 Reportedly, the main source of melatonin is the gastrointestinal tract, with estimated production over 400 times higher than that in the pineal gland. 12 The indoleamine has great pharmacological promise as an antioxidant enzyme that can scavenge free radicals, and protect from oxidative damage. 13,14 Previous studies has shown that melatonin can inhibit the proliferation of various human cancers, including leukemia, 15,16 hepatocarcinoma, 17 breast cancer, 18 colorectal cancer, 19,20 lung cancer, 21,22 and gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, melatonin functions in the regulation of various essential events in cellular physiology, including antioxidation, anti-inflammation and immune-cell activation, and is closely related to the occurrence of multiple diseases [ 6 , 7 , 8 , 9 ], and melatonin is also produced by a few other tissues besides the pineal gland, such as the liver, skin and small intestine [ 10 , 11 ]. Melatonin regulates cell physiology through receptor-dependent and -independent mechanisms, with the regulation occurring predominantly through the receptor-dependent mechanism: By binding to the receptor MT1 (encoded by MTNR1A ) or MT2 (encoded by MTNR1B ), melatonin can activate signaling pathways in cells and regulate physiological processes such as inflammation and the immune response [ 12 , 13 , 14 ]. Furthermore, melatonin and its metabolites are potent antioxidants that can bind directly to and neutralize peroxides produced in metabolism and thereby reduce cellular damage and act as powerful free-radical scavengers [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…-мелатонін пригнічує утворення ендотеліальних молекул адгезії, -зменшує жирову інфільтрацію ендотелію, -нейтралізує вільні радикали, -зменшує перекисне окиснення ліпідів, -модулює кліренс холестерину, -запобігає витоку електронів з дихального ланцюга мітохондрій [6,7].…”
Section: в п о м о щ ь п р а к т и к у ю щ е м у в р а ч уunclassified